Customer Orientation and Loyalty: Opinionistic Survey of Executives - Dr. Kanwal Jeet Singh (Ramanujan International Journal of Business and Research, 2017)
The most important objective of business organization in modern era is to satisfy the customers. Therefore, all the activities of each and every department must be customer oriented. Once the customers are satisfied from a particular product or service, they become loyal to that particular brand. The present study proposes to assess the ways used by general insurance companies to achieve customer orientation and importance given to various factors to build customer loyalty. The statistical't' test was employed on the responses of respondents, which included the opinions of executives with a well-structured questionnaire. The result of the study suggests that the customers' database, contact with customer and management of process to deliver services play an important role for customer orientation & complaint handling and clear point contact are the most important factors to build customer loyalty.